Proyecto de expansión de la comercializadora de telas "Flores" ubicado en el sur de Quito en la Provincia de Pichincha del Cantón Quito. - Moreno Rubio, Paúl Ramiro (2010)
This research develops in the trading of you the "Flowers", located in the center of the city of Quito, proposing a model of management by objectives for business expansion south of the City in the Chillogallo neighborhood, and thus meet the needs of its customers and the owner of it, considering aspects relating to the activity taking this business in our society.